THE IMPACT OF VILLAGE HEAD TERM EXTENSION ON VILLAGE PROGRESS: A VIEW FROM MASS MEDIA AND A VILLAGE IN SLEMAN, YOGYAKARTA - Saniya Dafin, Rahma Kintara; Nafila Rahman, Jasmine Hasna; Putra, Rafi Manggala; Aqil Ersan, Muhammad; Cahyati, Devy Dhian (Sriwijaya Crimen and Legal Studies, 2024)
The discourse on extending the village head’s term of office has triggered debates, especially following the revision of the Village Law in 2023, which now allows a 9-year term for two periods. However, according to constitutional norms, Indonesia is a State of Law (Rechtsstaat), which means limiting power by the law. This study aims to map the discourse surrounding this extension in online media and analyze the perceptions of Girikerto Village residents on the relationship between the extension and village progress, viewed through the lens of good governance. The research employs big data discourse network analysis and case studies to track dominant arguments and actors involved. The study reveals that political elites dominate the pro-extension discourse, arguing it stabilizes village politics, while community opposition highlights the risk of corruption and governance inefficiencies. Drawing on Bachrach and Baratz's elite theory, this research examines how elite groups influence decision-making processes. Additionally, it explores local perceptions, showing that residents reject the extension due to concerns over inclusiveness, fairness, and the effectiveness of governance. This study contributes to the debate by offering a nuanced analysis of village head term extensions' legal and governance implications.